Isaiah 10:1–4 and the welfare of the poor in Nkanuland, Enugu state, Nigeria - Ugwuewo, Chisom S. (HTS teologiese studies, 2025)
Over the centuries, history has shown that peasant members of society are drenched with various forms of marginalisation. These often come from the more privileged members of society and even the government. Studies have also shown that the religious sphere that ought to be the hope of the neglected poor has turned out to be like the political milieu in the secular world. Isaiah 10:1–4 spelt out punishment meted out for the violators of the rights of the peasant poor. The text indicates that the poor have been neglected in the past millennium. There have likely been no studies that took into cognisance the neglect of the poor from Isaiah 10:1–4 in the context of Nkanuland. Isaiah 10:1–4 examines the height at which the Jewish rulers exploit the poor at their various dispensations. However, such wicked acts by such leaders would not go unpunished. The poor are highly marginalised using different means by both religious and political leaders. The insufficient welfare provision for the poor has consequently led to ill health, death, vulnerability to danger, psychological stress, social alienation, poor education, poor diet and other related problems in Nigeria in general and Nkanuland in particular. The researcher, therefore, seeks to take a critical look at Isaiah 10:1–4 and applies its exegetical result(s) in Nkanu. It is argued that if the text is practically applied by religious and political leaders in Nkanuland, there would be improved welfare provision for the poor. Rhetoric and sociological approaches common to Old Testament exegesis are employed.Contribution: The researcher posits that Isaiah 10:1–4 would be a feasible solution to curb the incessant marginalisation of the peasant poor in Igboland in general and Nkanuland in particular. This would enhance both human and other aspects of development in Nkanuland.